Method of states on the basis of Kilchevskiy's equations for analysis of 3D steady-state oscillation - I. N. Stebenev; V. B. Pen'kov (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2011)
General solution of N. A. Kilchevskiy's equations for oscillating three-dimensional solids is constructed. Method of states for analysis of boundary-value problem about oscillations is proven, it is based on the following terms: states of medium (internal and boundary), space of states, scalar product, gilbert isomorphism.